Outcome four years after transcatheter foam sclerotherapy of the greater saphenous vein - Hahn, M.; Schulz, T.; Jünger, M. (Phlebologie, 2008)
The aim of the study was to evaluate the long-term results 4 years after a single-session, sonographically guided, transcatheter foam sclerotherapy. Patients, methods: We treated 20 patients with a total of 22 legs with varicoses of the greater saphenous vein (GSV, EpAsPr). Additional varicoses of the auxiliary veins of the GSV were sclerosed immediately afterwards. 20 legs or 91% in Hach stage III-IV, clinical stage C2-C5 and a mean GSV diameter of 9 mm (range: 7 to 13 mm) could be followed up 4 years later. Results: During the follow up period one leg showed clinical signs of recurrence and underwent surgery, two legs received a single additional sclerotherapy during the four years period. Examination four years after showed in 6 legs clinical signs of recurrence without notice of clinical symptoms by the patients. This gives a clinical recurrence rate of 40% (8 of 20 patients). Duplex sonography showed flow in the region of the saphenofemoral junction in a total of 13 legs (65% of the reexamined GSVs) with an average vessel diameter of 3.7 ± 1.6mm (range 2 to 7 mm). Retreatments in 3 GSV of the 6 clinically relapsed GSV by a single injection of sclerosing foam showed an occlusion in 100% two weeks after. Conclusion: Transcatheter foam sclerotherapy of the GSV shows better clinical long-term results compared to known data of liquid sclerotherapy. Sonographically detected recurrency of the GSV could easily be retreated by a single session of foam sclerotherapy. Foam sclerotherapy is a promising and seriously to be taken option in the treatment of the insufficient GSV.
Keywords: Foam sclerotherapy; endoluminal therapy; insufficiency of the deep veins; long-term results